Working with programming to learn logic concepts - Santos, Raquel (2022)
Although technology has grown exponentially and programming is no longer a novelty, its integration in a school context, which goes beyond knowing how to program, is very low. Many authors argue that learning to program must happen in context and, preferably, for students to learn concepts from different areas. For this to happen in the classroom, it is necessary for teachers to have similar experiences during their teacher training. This paper presents a case study of a class in the first year of their Teacher Education Program, in which future kindergarten and elementary teachers approached concepts of Boolean logic through programming. A description of the experience is made, and students’ perspectives, learning and difficulties are presented throughout the experience. The results are positive, both in terms of programming knowledge and in relation to the attitudes and perspectives of future kindergarten and elementary teachers regarding their use in the classroom.